Mémoires des sens et des paysages littoraux sur l’île d’Iaai (Ouvéa en Nouvelle-Calédonie) - Catherine Sabinot; Valentine Boudjema; Matthieu Le Duff; Pascal Dumas (VertigO)
In New-Caledonia the kanak tribes of Iaai island are now precious reminders of coastal morphological changes. In the context of coastal risks, as erosion, became environmental and institutional matters increasingly integrated to the land use development , to be involved in islanders memory pertaining to landscape transition and their actual coastal landscape representation provides means of handling territory link including its sensorial and symbolic dimensions. If vision is a sens rallied by the inhabitants in order to characterize the result of erosion on landscape, therefore, smell, hear and feel are sensorial landscape evolution arguments ». This paper discusses the values assigned to the Gööny coastline and the construction process of a memory landscape that relies on memories about cultural and religious activities, on toponymy reminding the beach morphology, and on tactile memory as sand texture. In this way, we will demonstrate how sense memories of landscape reflects the link between the changes of a physical environment and societal transformations, and are relevant tools to produce development projects that engage the sensitives perceptions of residents.